2012
DOI: 10.1002/zoo.21000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Regurgitation and Reingestion in Orangutans Housed in North American Zoos and an Examination of Factors Influencing its Occurrence in a Single Group of Bornean Orangutans

Abstract: Very little research has explored regurgitation and reingestion (R/R) in orangutans. We first aimed to determine the prevalence of R/R in the North American zoo population through a survey of accredited institutions. We report the prevalence of R/R in orangutans >4 years of age as 35% with some sex and species differences. Additionally, survey respondents reported fruit and sweet foods as the most common triggers of R/R. We also explored rates of R/R in a single group of Bornean orangutans at Cleveland Metropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
(39 reference statements)
0
21
1
Order By: Relevance
“…Similarly, a recent survey on N=154 Orangutans in the Association of Zoos and Aquariums Species Survival Plan® (SSP) population in North American zoos, found that the youngest Orangutans to engage in R/R were 5 years old (Cassella et al, 2012). In that study, the overall prevalence of R/R was 32% (N=49 out of 154 animals), which rose to 36% (N=60) after removing the 17 Orangutans aged 4 years or younger from the analysis.…”
Section: Prevalence Of R/r In Great Apesmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, a recent survey on N=154 Orangutans in the Association of Zoos and Aquariums Species Survival Plan® (SSP) population in North American zoos, found that the youngest Orangutans to engage in R/R were 5 years old (Cassella et al, 2012). In that study, the overall prevalence of R/R was 32% (N=49 out of 154 animals), which rose to 36% (N=60) after removing the 17 Orangutans aged 4 years or younger from the analysis.…”
Section: Prevalence Of R/r In Great Apesmentioning
confidence: 91%
“…Hill, unpubl. data), followed by filled cheeks and mastication, and so the behaviour could potentially be easily missed if the observer is not well-practised in recognising it (Cassella et al, 2012).…”
Section: R/r In Non-human Great Apesmentioning
confidence: 99%
See 2 more Smart Citations
“…R/R has been recorded among captive primates (macaques, baboons and the apes) [Baker and Easley, 1996], but ours is the first evidence of this phenomenon in prosimians. R/R behaviour has been linked to boredom in captivity, space restriction, stress, low levels of stimulation, suboptimal diet [Capitanio, 1986;Lukas, 1999;Cassella et al, 2012] or the absence of feeding opportunities after the daily food portion had been served and eaten [Baker and Easley, 1996]. The number of R/R events in our study was low (20 occurrences), they were noticed more frequently for the female, and most events were observed when it rained -usually between the 3rd and 4th h of the animals' activity.…”
Section: Activity Patterns Of Tarsius Syrichtamentioning
confidence: 99%